SURVEI KEBUGARAN JASMANI SISWA SMP NEGERI 2 KERINCI PADA KEGIATAN EKSTRAKURIKULER FUTSAL - Praja, Aldino Wira (Journal Score, 2026)
This study aimed to analyze the physical fitness level of students at SMP Negeri 2 Kerinci. The research employed a survey method with data collected through physical fitness tests and measurements. A descriptive quantitative approach was used, and the sample consisted of the entire population through a total sampling technique, involving 23 students. The results of the study showed that in the 50-meter sprint test, 1 student (8%) was categorized as Very Good, 10 students (77%) as Good, and 2 students (15%) as Moderate. In the standing broad jump test, 3 students (23%) were categorized as Good, 9 students (69%) as Moderate, and 1 student (8%) as Poor. In the sit-up test, 8 students (62%) were categorized as Good, while 5 students (38%) were categorized as Moderate. In the shuttle run test, 3 students (23%) were categorized as Good, 9 students (69%) as Moderate, and 1 student (8%) as Poor. The novelty of this study lies in providing a profile of the physical fitness level of futsal extracurricular participants at SMP Negeri 2 Kerinci, which can serve as a basis for designing more targeted and effective physical training programs. The study concluded that the physical fitness level of students participating in the futsal extracurricular program at SMP Negeri 2 Kerinci falls within the Good category.